Simulation: social work education in a third place. - Meredith, Cathryn; Heslop, Philip; Dodds, Christina (Social Work Education, 2023)
The curriculums of social work education are traditionally divided, with professional and theoretical knowledge taught largely in the classrooms of academia, whilst practical skills and experience are developed mostly in workplace settings. This paper locates simulation in Lev Vygotsky's sociocultural theory and Paulo Freire's pedagogy, considering its potential to offer social work education a third place, complementary to, yet unique and distinct from the first place of academy and the second place of placement. The authors present findings from the first stage of their evaluation of the introduction of simulation to social work curriculums at a UK university. Narrative responses are presented across six, overarching themes: the pedagogical approach; authenticity; engineered failure; applying theory in practice; developing practice skills; reflection and feedback. The data demonstrates that respondents valued opportunities for deliberate practice which enabled them to experience emotional responses and learn from their mistakes without negative consequence. Although these findings predate COVID 19, they are ever-more relevant as social work education reconsiders how to reach, teach, and engage social work students during the pandemic and beyond.